2014
DOI: 10.1186/1297-9686-46-25
|View full text |Cite
|
Sign up to set email alerts
|

Detection of QTL controlling digestive efficiency and anatomy of the digestive tract in chicken fed a wheat-based diet

Abstract: BackgroundImproving digestive efficiency is a major goal in poultry production, to reduce production costs, make possible the use of alternative feedstuffs and decrease the volume of manure produced. Since measuring digestive efficiency is difficult, identifying molecular markers associated with genes controlling this trait would be a valuable tool for selection. Detection of QTL (quantitative trait loci) was undertaken on 820 meat-type chickens in a F2 cross between D- and D+ lines divergently selected on low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 31 publications
3
29
0
1
Order By: Relevance
“…The results of genetic estimation showed that JL and IL have high heritability, while DL has moderate heritability. These results were similar to those of a previous study in which the heritability of the relative intestine length in chicken fed a wheat-based diet was moderate (h 2 ¼ 0.37) (Tran et al 2014). Among the three traits, the genetic correlations were high, but the phenotypic correlations were not, indicating that these traits were greatly influenced by environmental factors.…”
Section: Estimation Of Contribution To Phenotypic Variation (Cpv)supporting
confidence: 89%
“…The results of genetic estimation showed that JL and IL have high heritability, while DL has moderate heritability. These results were similar to those of a previous study in which the heritability of the relative intestine length in chicken fed a wheat-based diet was moderate (h 2 ¼ 0.37) (Tran et al 2014). Among the three traits, the genetic correlations were high, but the phenotypic correlations were not, indicating that these traits were greatly influenced by environmental factors.…”
Section: Estimation Of Contribution To Phenotypic Variation (Cpv)supporting
confidence: 89%
“…Finally, genomic tools could be useful as was previously highlighted that some genomic regions were linked with FE characteristics in livestock species (Chen et al 2011;Wolc et al 2013;Al-Husseini et al 2014;Tran et al 2014). However, nothing has been reported to date on fish to our knowledge.…”
Section: Neuropeptides and Hormonesmentioning
confidence: 91%
“…The divergent selection experiment started from a pure male line from the SASSO breeding company, used as the father of the medium-growth crossbred commercial chickens. The F2 population, created to detect the QTLs for digestive efficiency, has been described in Tran et al [ 17 ]. Before crossing, the D+ and D- populations presented wide differences in feed and digestive efficiency (30 to 40%) [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%